Student Resilience in Response to Local Government Policies During the COVID-19 Pandemic: A Case Study of Al Ma’ruf Private Islamic Senior High School, Denpasar - Ajeng Widjaya Pangesti; Ngurah Anom Kumbara; Ni Made Ras Amanda Gelgel (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines student resilience at MAS Al Ma'ruf Denpasar in response to Denpasar City Government's online learning policies during the COVID-19 pandemic. Employing a qualitative approach through in-depth interviews with students, teachers, and policymakers, the research identifies patterns of student adaptation to distance learning challenges. The descriptive qualitative methodology incorporates data collected via observation, in-depth interviews with stakeholders, and literature review. Conducted at MAS Al Ma'ruf Denpasar, the study utilizes purposive sampling for informant selection. Inductive data analysis reveals student adaptation strategies to technological limitations and academic workload. Key findings demonstrate that while initial resistance emerged due to technological constraints, excessive assignments, and limited social interaction, students progressively developed resilience through technological adaptation, self-regulated time management, and social support utilization. Critical resilience-enabling factors include: (1) systemic school support through teacher training and infrastructure provision; (2) participatory communication among school, student, and parent networks; and (3) curriculum-integrated adaptation values. Theoretical analysis through Foucault and Bourdieu's lenses reveals student resilience as both a response to power relations in educational policy and an outcome of negotiation between student habitus and available socio-economic capital. Policy implications emphasize three requirements for inclusive education: (1) flexible learning methods based on student realities; (2) equitable digital infrastructure strengthening; and (3) sustainable feedback mechanisms for active student participation in decision-making. These findings enrich crisis education discourse by proposing a school-community based resilience model adaptable to other emergency contexts.